A Review of Entering Research: A Facilitator’s Manual<source>Entering Research: A Facilitator’s Manual</source>; <edition>1st ed.</edition>; <person-group person-group-type="author"> <name name-style="western"> <surname>Branchaw</surname> <given-names>Janet</given-names> </name> <name name-style="western"> <surname>Pfund</surname> <given-names>Christine</given-names> </name> <name name-style="western"> <surname>Rediske</surname> <given-names>Raelyn</given-names> </name> </person-group>; ( <year>2010</year>). <publisher-name>W.H. Freeman and Company</publisher-name>, <publisher-loc>New York</publisher-loc>. <fpage>284</fpage> pages. - Lee E. Hughes (American Society for Microbiology, 2011)
Review of: Entering Research: A Facilitator’s Manual; 1st ed.; Janet Branchaw, Christine Pfund, and Raelyn Rediske; (2010). W.H. Freeman and Company, New York. 284 pages.